Akulturasi Arsitektur Kolonial terhadap Perbedaan Iklim di SDN Ditotruman Lumajang dan Rumah Dinas Bakorwil Madiun - Roosandriantini, Josephine; Poernama, Jessica Aprilia; Setiawan, Ferdinard Hendra; Limantara, Krisnina Dohan (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
The phenomenon of acculturation between Dutch and Indonesian cultures occurs a lot in colonial cultural heritage objects. This condition is a description of a Dutch building during the colonial period. Differences in climate are fundamental between the Netherlands and Indonesia, colonial buildings in Indonesia exist as a form of adaptation to the climate in Indonesia. Adaptations to colonial buildings in the form of openings, roof shapes, and ceiling heights. Acculturation can be seen in spatial patterns, and column shapes. The method in this study is descriptive qualitative, and data collection is a literature study related to colonial architecture. The objects in the field have colonial architectural characteristics in the exterior and interior elements. The purpose of this research is to analyze the architectural elements of colonial architecture in Indonesia. The results of the research can add insight into the forms of adaptation to climate in colonial architecture.